The COVID-19 Family Stressor Scale: Validation and Measurement Invariance in Female and Male Caregivers - Prime, Heather; Wade, Mark; May, Shealyn S.; Jenkins, Jennifer M.; Browne, Dillon T. (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic has raised significant concerns regarding the effect of social disruptions on parental mental health, family well-being, and children’s adjustment. Due to the pace of the pandemic, measures of pandemic-related disruption have not been subject to rigorous empirical validation. To address this gap, a multi-national sample (United Kingdom, 76%; United States, 19%; Canada, 4%, and Australia, 1%) of 372 female caregivers and 158 male caregivers of 5–18-year-old children was recruited online. Participants completed a survey including a 25-item scale indexing disruption in finances, basic needs, personal and family welfare, career/education, household responsibilities, and family relationships related to the pandemic. An exploratory factor analysis yielded an optimal three-factor solution: factors included Income Stress (5 items related to income, debt, and job loss; loadings ranged from .57 to .91), Family Stress (7 items related to family altercations and child management; loadings from .57 to .87), and Chaos Stress (4 items related to access to supplies, crowded shopping areas, news coverage; loadings from .53 to .70). Multiple-group confirmatory factor analysis demonstrated measurement invariance of each factor across female and male caregivers, indicating that factor structure, loadings, and thresholds were equivalent across groups. Composites reflective of each factor were computed, and Mann-Whitney U tests indicated that that female caregivers consistently scored higher than male caregivers on COVID-19 stressors related to income, family, and chaos. Finally, concurrent validity was demonstrated by significant bivariate correlations between each scale and caregiver, family, and child outcomes, respectively. This demonstrates the validity of the COVID-19 Family Stressor Scale for use with female and male caregivers in family-based research. The current sample was predominantly White-European, married/common-law, and had at least some post-secondary education. Additional sampling and validation efforts are required across diverse ethnic/racial and socioeconomic groups.